Crown ether-like compound, electrolyte containing crown ether-like compound and application of crown ether-like compound in secondary battery
By designing crown-like ether compounds with large cavity structure and nitrogen oxide structure as electrolyte additives, the problem of insufficient sodium profiling behavior and ion migration ability in sodium ion batteries is solved, and the effect of high ion conductivity and prolonging life is achieved. The synthesis is simple and suitable for large-scale preparation.
Patent Information
- Application Number
- CN202411666887.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing sodium-ion batteries are prone to sodium profiling during charging and discharging, which affects the battery's cycle life and ion migration ability. It is difficult to prepare crown ether on a large scale, limiting its application in industrialization.
A crown-like ether compound has a large cavity structure and an nitrogen oxide structure, which can form an ion dipole with sodium ions, improve the solvation structure and enhance the migration ability of ions. As an additive to the electrolyte, this type of crown ether compound can reduce the concentration of sodium ion on the surface of the electrode and avoid sodium profiling. It also has a simple synthesis process and is relatively low in cost.
It effectively avoids sodium analysis behavior on the negative electrode surface, improves the cycle life and ionic conductivity of the battery, overcomes the disadvantage that crown ether is difficult to prepare on a large scale, and has the potential for industrial production.
Smart Images

Figure CN119504575A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of secondary battery electrolytes, in particular to a crown ether-like compound, an electrolyte containing the crown ether-like compound and the application thereof in a secondary battery, including a non-aqueous electrolyte and a sodium ion battery containing the non-aqueous electrolyte. Background Art
[0002] Compared with traditional batteries, lithium-ion batteries (LIBs) with high energy density and high operating voltage have become a more convenient energy storage device. Lithium-ion batteries are widely used in many electronic devices, especially in new energy electric vehicles in recent years, which has led to its rapid development. However, the storage of lithium ions in batteries is small, and the cost of raw materials is relatively high. It is quite necessary to develop a new generation of energy batteries. Among them, sodium ions, which are in the same family as lithium ions, have become the focus of people's attention. Studies have shown that sodium ions have similar properties to lithium ions in some forms and have considerable reserves in nature. Therefore, sodium ion batteries have the potential to become a substitute for lithium ion batteries.
[0003] In the past two years, research on sodium-ion batteries has focused on the composition and optimization of the electrode-electrolyte interface film. By optimizing the electrolyte additives and electrolyte solvent ratio formula, a stable electronically insulating passivation film is formed on the electrode surface to avoid further decomposition of the electrolyte, consumption of sodium ions and gas production, which leads to a decrease in battery capacity, thereby extending the service life. During the battery charging and discharging process, the sodium-ion battery will pass through the electrolyte between the positive and negative electrodes to achieve back and forth migration. The migration process of ions is also very important for the performance of the battery. The migration process of ions involves the solvation and desolvation of sodium ions.
[0004] However, research on the solvation structure of ions is still insufficient. At present, the default theory for the solvation structure includes: the solvent acts as a continuous homogeneous medium, using electrostatic forces, van der Waals forces and coordination bonds formed with cations to confine the cations in the middle, forming a solvation shell, and migrating in channels composed of free solvated molecules and anions. The solvation structure of ions will significantly affect the ionic conductivity, battery capacity and cycle life of the battery. Therefore, optimizing the composition of cations, solvent molecules and anions to achieve the adjustment of the solvation structure can effectively improve the performance of the battery.
[0005] As a compound with a large cavity structure, crown ether has a certain ion coordination ability. Its coordination with sodium ions can wrap the sodium ions in the center of the molecule, thereby increasing the distance between the sodium ions and the anions, which is convenient for improving the desolvation ability of the ions. Aliphatic crown ethers have good coordination ability with lithium ions and are compatible with the electrolyte negative electrode. Studies have shown that the introduction of crown ethers in lithium metal batteries effectively reduces the concentration of lithium ions on the electrode surface, avoids the generation of large crystal nuclei, and avoids lithium precipitation behavior during the operation of lithium-ion batteries. However, crown ethers, a large ring-shaped molecule, need to be highly diluted during synthesis and are difficult to prepare on a large scale, which increases the cost of crown ethers. Summary of the invention
[0006] In view of this, the object of the present invention is to provide a novel crown ether-like compound, an electrolyte containing the crown ether-like compound and the application thereof in a secondary battery. The crown ether-like compound provided by the present invention is applied in a secondary battery, and not only has the sodium precipitation-avoiding effect of the crown ether, but also has a strong electron-withdrawing ability, and can produce an ion dipole effect with sodium ions, thereby effectively improving the solvation structure and enhancing the migration ability of ions. In addition, the synthesis process is simple, the cost is low, and it has the potential for industrial production.
[0007] One of the purposes of the present invention is to provide a crown ether-like compound having a structure of Formula I or Formula II:
[0008]
[0009] The present invention provides a method for preparing a crown ether-like compound, comprising the following steps:
[0010] The pentaerythritol is subjected to a substitution reaction with an ortho-halogenated nitrogen-containing heterocyclic substance to obtain an intermediate; the ortho-halogenated nitrogen-containing heterocyclic substance is an ortho-halogenated pyridine or an ortho-halogenated pyrrole;
[0011] The intermediate is subjected to quaternary ammonium oxidation with an oxidant to obtain a crown ether-like compound as shown in Formula I or Formula II;
[0012]
[0013] The second object of the present invention is to provide an electrolyte containing a crown ether-like compound, comprising a non-aqueous organic solvent, a sodium salt and an additive, wherein the additive is the crown ether-like compound described above or the crown ether-like compound obtained by the preparation method described above.
[0014] Furthermore, the sodium salt is selected from at least one of sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium bis(oxalatoborate), sodium difluorophosphate, sodium difluorooxalatoborate and sodium difluorobis(oxalatophosphate).
[0015] Furthermore, the non-aqueous organic solvent is one or more of organic esters, C1-10 alkyl ethers, cyclic ethers, sulfones, dinitriles, and ionic liquids.
[0016] Furthermore, the organic esters are at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, 1,4-butyrolactone, methyl formate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate and ethyl butyrate; the C1-10 alkyl ethers are at least one of dimethyl ether, diethyl ether and methyl ethyl ether; the dinitriles are at least one of adiponitrile, succinonitrile and glutaronitrile; the sulfones are at least one of dimethyl sulfoxide and cyclopentane sulfone; and the ionic liquids are at least one of imidazole and pyrrole ionic liquids.
[0017] Furthermore, the non-aqueous organic solvent accounts for 60-85% of the weight of the electrolyte. Preferably, the non-aqueous organic solvent accounts for 75-85% of the weight of the electrolyte.
[0018] Furthermore, the sodium salt accounts for 8-25% of the weight of the electrolyte.
[0019] The third object of the present invention is to provide a sodium ion battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte is the electrolyte containing the crown ether-like compound as described above.
[0020] Furthermore, the active material of the positive electrode is selected from layered oxides, Prussian blue or polyanions; the present invention prefers layered oxide positive electrode active materials.
[0021] Furthermore, the active material of the negative electrode is selected from at least one of graphite, hard carbon, silicon-carbon composite material and silicon monoxide; these materials are applied alone or in combination in the present invention, and the present invention preferably selects hard carbon as the active material of the negative electrode.
[0022] Furthermore, the separator in the sodium ion battery is selected from polypropylene or polyethylene separator.
[0023] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a novel compound similar to the structure of a crown ether substance, called a crown ether-like compound, whose structure is shown in Formula I or Formula II. This type of crown ether compound is used as an additive to improve the solvation structure of ions from the perspective of ion solvation-desolvation, enhance the ionic conductivity of the electrolyte, and avoid the problem of sodium precipitation of the negative electrode material. The non-aqueous electrolyte containing the above-mentioned crown ether-like additive provided by the present invention can be applied to secondary batteries to reduce the sodium ion concentration on the electrode surface, avoid sodium precipitation behavior, and extend the working life of the battery. The electrolyte containing the crown ether-like additive developed by the present invention overcomes the disadvantage that crown ethers cannot be prepared on a large scale. The prepared electrolyte can effectively avoid the sodium precipitation behavior on the negative electrode surface and has high ionic conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a picture of the LSV curve of the electrolyte in Example 5 of the present invention;
[0025] Figure 2 The long cycle performance test results of the assembled battery in Example 5 of the present invention;
[0026] Figure 3 This is the electrochemical impedance test curve of the electrolyte in Example 5 of the present invention. DETAILED DESCRIPTION
[0027] In order to enable those skilled in the art to better understand the technical solution of the present invention, the purpose, technical solution and beneficial effects of the present invention are further illustrated by specific embodiments below. The specific embodiments of the present invention are further illustrated in conjunction with examples, but do not constitute any limitation to the present invention. It should be noted that the specific embodiments described herein are only for the purpose of illustrating and explaining the present invention, and are not limited to the present invention. If the specific conditions are not specified in the embodiments, they can be carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0028] At present, the optimization of sodium ion battery additives is mostly focused on optimizing the formation of excellent and stable electrode passivation films, but there are not many studies on the solvation and desolvation processes during the migration of sodium ions. During the operation of the battery, if the additive has a strong bonding ability to ions, it can effectively simplify the solvation of sodium salts and simplify the migration in the electrolyte. However, if the bonding ability is too strong, the desolvation process of ions becomes difficult, so it is not conducive to the transmission of ions to the electrode. The conflict between the two makes it difficult to design excellent additives or solvents. Therefore, this also creates the reason why there are few molecular designs for solvation-desolvation additives. Crown ether additives have a large cavity structure, form coordination with cations, and squeeze out anions with larger molecular structures, effectively separating cations and anions, and improving ion mobility. However, crown ethers are difficult to produce on a large scale due to the limitations of synthesis, which inhibits their application in industrialization.
[0029] In a first aspect of an embodiment of the present invention, a crown ether-like compound is designed, having a structure of Formula I or Formula II:
[0030]
[0031] The crown ether-like compound shown in Formula I or Formula II as an additive retains the advantages of crown ether, can optimize the sodium ion concentration on the electrode surface, avoid the deposition of sodium to form dendrites and pierce the diaphragm to cause a short circuit, thereby extending the life of the battery. In addition, its large cavity structure forms coordination with sodium ions, increases the distance between cations and anions, reduces the solvation energy of ions, and the nitrogen-oxygen structure formed by pyridine or pyrrole has a strong ion coupling effect when coordinated with sodium ions, further reduces the solvation energy of ions, allows ions to quickly jump between coordination sites, and increases the number of ion migration.
[0032] Accordingly, an embodiment of the present invention provides a method for preparing a crown ether-like compound, comprising the following steps:
[0033] The pentaerythritol is subjected to a substitution reaction with an ortho-halogenated nitrogen-containing heterocyclic substance to obtain an intermediate; the ortho-halogenated nitrogen-containing heterocyclic substance is an ortho-halogenated pyridine or an ortho-halogenated pyrrole;
[0034] The intermediate is subjected to quaternary ammonium oxidation with an oxidant to obtain a crown ether-like compound as shown in Formula I or Formula II;
[0035]
[0036] Some embodiments of the present invention synthesize a crown ether-like compound having a structure of Formula I, and the reaction formula thereof is as follows:
[0037]
[0038] Wherein, the ortho-halogenated nitrogen-containing heterocyclic substance is 2-bromopyridine, and the structure is as follows; DMF is N,N-dimethylformamide, NaH is sodium hydride, m-CPBA represents meta-chloroperbenzoic acid, and CHCl3 represents chloroform;
[0039]
[0040] In the embodiment of the present invention, a certain amount of pentaerythritol is added to a reactor, and NaH and solvent DMF can be added in multiple times. The obtained mixture is stirred at room temperature for a certain time, and then 2-bromopyridine is slowly added, preferably heated to 80° C. and refluxed overnight to obtain a reaction solution. After post-treatment processes such as extraction, washing, and purification, an intermediate having a crown ether-like cavity structure is obtained.
[0041] The reaction temperature range for preparing the intermediate described in the embodiment of the present invention is 80-120° C., preferably 80° C.; the reaction time can be 16-24 hours, preferably 24 hours.
[0042] In some embodiments of the present invention, the molar ratio of pentaerythritol to 2-bromopyridine is 1:1.2;
[0043] The solvent in the embodiment of the present invention can be one or more of N,N-dimethylformamide, tetrahydrofuran and dichloromethane, preferably N,N-dimethylformamide.
[0044] The catalyst described in the embodiment of the present invention is a strong base, including sodium methoxide, calcium hydride and sodium hydride, etc. Sodium hydride is preferably used as the catalyst, and the feed equivalent is preferably 1.2.
[0045] In the embodiment of the present invention, the intermediate, chloroform and m-CPBA are added to a reaction vessel, argon is blown for 30 minutes, and the reaction is stirred at room temperature overnight. Water is added to quench the reaction, and the resulting reaction solution is washed, filtered, concentrated and purified by column chromatography multiple times to obtain a crown ether compound shown in formula I.
[0046] In some other embodiments, 2-bromopyridine can be replaced by 2-bromopyrrole to prepare the crown ether-like compound shown in Formula II. The synthesis process of the crown ether-like compound in the embodiment of the present invention is simple, low in cost, and conducive to large-scale production.
[0047] In a second aspect, an embodiment of the present invention provides an electrolyte containing a crown ether-like compound, comprising a non-aqueous organic solvent, a sodium salt and an additive, wherein the additive is the crown ether-like compound described above or the crown ether-like compound obtained by the preparation method described above.
[0048] In an embodiment of the present invention, the electrolyte is a non-aqueous sodium ion electrolyte with high ionic conductivity, which includes a sodium salt and the above-mentioned crown ether-like compound additive. Compared with the prior art, the electrolyte prepared by the crown ether-like additive described in the present invention exhibits the characteristics of crown ethers in the battery on the one hand - optimization of the solvation structure to avoid sodium precipitation. On the other hand, the crown ether-like structure avoids the disadvantage that crown ethers are not conducive to large-scale synthesis. Different from ordinary crown ethers, the nitrogen oxide structure is applied therein, and its strong electron-withdrawing ability is utilized to have ion coupling with sodium ions, thereby enhancing the solvation ability of ions and making the electrolyte have high ionic conductivity.
[0049] The electrolyte of the embodiment of the present invention includes a sodium salt electrolyte, and the sodium salt can be selected from at least one of sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), sodium tetrafluoroborate (NaBF4), sodium bistrifluoromethylsulfonyl imide (NaTFSI), sodium bisfluorosulfonyl imide (NaFSI), sodium bisoxalate borate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorooxalate borate (NaODFB) and sodium difluorodioxalate phosphate (NaDODFP), preferably sodium hexafluorophosphate. Preferably, the content of the sodium salt accounts for 8-25% of the weight of the electrolyte, more preferably 10-23%, for example, 12%, 15%, 16%, 18%, 20%, etc.
[0050] Furthermore, the non-aqueous organic solvent in the electrolyte may be one or more of organic esters, C1-10 alkyl ethers, cyclic ethers, sulfones, dinitriles, and ionic liquids. Among them, the organic esters are preferably at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, 1,4-butyrolactone, methyl formate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, and ethyl butyrate; carbonate solvents such as propylene carbonate are commonly used.
[0051] The C1-10 alkyl ether non-aqueous solvent is preferably at least one of dimethyl ether, diethyl ether and methyl ethyl ether; the dinitriles are preferably at least one of adiponitrile, succinonitrile and glutaronitrile; the sulfones are preferably at least one of dimethyl sulfoxide and cyclopentane sulfone; the ionic liquids are preferably at least one of imidazole and pyrrole ionic liquids.
[0052] Furthermore, the non-aqueous organic solvent accounts for 60-85% by weight of the non-aqueous electrolyte. Preferably, the non-aqueous organic solvent accounts for 75-85% by weight of the non-aqueous electrolyte.
[0053] In the embodiment of the present invention, the crown ether-like compound can be dissolved in a non-aqueous organic solvent at a ratio of 1 to 3% wt, preferably 1% wt; then sodium salt is added, stirred and dissolved at room temperature, and fully mixed until a transparent homogeneous phase is obtained, thereby obtaining the non-aqueous electrolyte with high ionic conductivity containing the crown ether-like additive.
[0054] The third aspect of the embodiments of the present invention further provides a sodium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte is the electrolyte containing the crown ether-like compound as described above.
[0055] Wherein, the positive electrode and the negative electrode both contain corresponding active materials, and the present invention has no special restrictions on other electrode compositions. The active material of the positive electrode is preferably selected from layered oxides, Prussian blue or polyanions; more preferably layered oxides. The active material of the negative electrode can be selected from at least one of graphite, hard carbon, silicon-carbon composite materials and silicon monoxide; these materials are applied to the present invention alone or in combination, and the present invention preferably selects hard carbon as the active material of the negative electrode.
[0056] In addition, the separator in the sodium ion battery is selected from polypropylene (PP) or polyethylene (PE) separator, preferably PE separator, which are conventional battery components. In the embodiment of the present invention, the positive electrode, separator, negative electrode and the non-aqueous electrolyte containing the crown ether-like additive can be conventionally assembled; the assembly form is the assembly form of a conventional soft-pack battery, the separator and the positive and negative electrodes are alternately stacked, encapsulated, aluminum is used as the current collector of the positive and negative electrodes, and the liquid is injected by artificial injection, and finally the sodium ion battery is sealed and tested.
[0057] As for the application scope of the electrolyte with high electrochemical stability described in the present invention, the electrolyte can be applied to the field of secondary batteries such as sodium ion batteries (including aqueous sodium ion batteries), sodium metal batteries, sodium sulfur batteries, etc. The high ionic conductivity electrolyte developed by the present invention has the characteristics of high ionic conductivity, low electrochemical impedance, and long cycle life, and the additive synthesis is simple and can be synthesized on a large scale.
[0058] In order to solve the sodium precipitation behavior of existing sodium ion batteries and optimize the solvation-desolvation process during ion migration, thereby improving ion conductivity, the present invention designs a crown ether-like compound with a large cavity structure formed by combining an aromatic ring and a chain ether. The crown ether-like compound of the present invention is easy to synthesize and suitable for large-scale preparation as an additive molecule for the electrolyte.
[0059] The embodiment of the present invention is based on crown ethers, and adopts a crown ether-like method to avoid the disadvantage that crown ethers are difficult to synthesize on a large scale. Nitrogen oxides are introduced, and their ionic coupling with sodium ions is utilized to enhance the bonding ability of ions and improve the solvation structure of ions, so that the electrolyte containing such crown ether additives has high ionic conductivity and avoids sodium precipitation at the negative electrode interface. The non-aqueous electrolyte of the present invention is used to make a sodium ion battery, and the ionic conductivity is significantly improved, which is specifically manifested in that the overall cycle life of the battery is greatly improved, especially the sodium ion battery with layered oxide positive electrode materials.
[0060] The following is a specific implementation description of the examples. If no specific conditions are specified in the examples, the experiment can be carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without specifying the manufacturer are all conventional products available on the market.
[0061] Synthesis of compounds
[0062] Example 1
[0063]
[0064] Reaction process of compound 1:
[0065] 0.27 g of pentaerythritol and 30 mL of DMF were added into a three-necked flask, and 0.14 g of NaH was added three times. The mixture was stirred at room temperature for one hour, and then 1.54 g of 2-bromopyridine was slowly added dropwise. After the addition was completed, the temperature was raised to 80°C and refluxed overnight. The reaction was confirmed to be complete by tapping the plate.
[0066] Post-processing process:
[0067] After cooling to room temperature, deionized water was added to quench the reaction, poured into ice water, extracted three times with ethyl acetate, the organic phases were combined, washed three times with deionized water, washed three times with saturated brine, anhydrous magnesium sulfate was added to remove water, filtered, the liquid phase was concentrated by rotary evaporation, and purified by column chromatography with n-hexane: ethyl acetate = 1:1 (volume ratio) as the eluent to obtain 1.16 g of a white solid with a yield of 65%.
[0068] H NMR spectrum data of compound 1: 1 H NMR (500MHz, Chloroform-d) δ7.70 (dd, J=5.0, 1.2Hz, 4H), 7.35 (td, J=8.0, 1.2Hz, 4H), 6.63 (dd, J= 8.0,1.0Hz,4H),6.39(ddd,J=8.0,5.1,1.1Hz,4H),4.44(d,J=12.3Hz,3H),4.28(d,J=12.3Hz,3H).
[0069] Example 2
[0070]
[0071] Reaction process of compound 2:
[0072] 0.435 g of compound 1, 10 mL of chloroform and 0.504 g of m-CPBA were added to a three-necked flask, and argon was bubbled for 30 minutes. The mixture was stirred at room temperature and reacted for 12 hours.
[0073] Post-processing process:
[0074] Water was added to quench the reaction, and the product was extracted three times with ethyl acetate. The organic phases were combined, washed three times with deionized water and three times with saturated brine, anhydrous magnesium sulfate was added to remove water, the product was filtered, the liquid phase was concentrated by rotary evaporation, and the product was purified by column chromatography using n-hexane: ethyl acetate = 1:1 (volume ratio) as the eluent to obtain 0.45 g of a white solid with a yield of 91%.
[0075] Compound 2 is the crown ether-like compound, and its H NMR spectrum data is: 1 H NMR (500MHz, Chloroform-d) δ8.34(s,1H),7.63(d,J=12.5Hz,2H),7.24(s,1H),4.36(d,J=12.5Hz,1H),4.23(d,J=12.5Hz,1H).
[0076] Example 3
[0077]
[0078] Reaction process of compound 3:
[0079] 0.27 g of pentaerythritol and 30 mL of DMF were added to a three-necked flask, and 0.14 g of NaH was added three times. The mixture was stirred at room temperature for one hour, and then 1.45 g of 2-bromopyrrole was slowly added dropwise. After the addition was completed, the temperature was raised to 80°C and refluxed overnight. The reaction was confirmed to be complete by tapping the plate.
[0080] Post-processing process:
[0081] After cooling to room temperature, deionized water was added to quench the reaction, poured into ice water, extracted three times with ethyl acetate, the organic phases were combined, washed three times with deionized water, washed three times with saturated brine, anhydrous magnesium sulfate was added to remove water, filtered, the liquid phase was concentrated by rotary evaporation, and purified by column chromatography with n-hexane: ethyl acetate = 1:1 (volume ratio) as the eluent to obtain 1.16 g of a white solid with a yield of 65%.
[0082] H NMR spectrum data of compound 3: 1H NMR(500MHz,Chloroform-d)δ7.31-7.34(dd,J=5.0,1.2Hz,6H),7.22(td,J=8.0,1.2Hz,6H),6.56(dd,J=8.0,1.0Hz,6H),4.63(d,J=12.3H z, 6H), 4.39d (J = 12.3Hz, 2H), 4.33 (d, J = 12.3Hz, 2H), 4.20 (d, J = 5.0, 1.2Hz, 1H), 4.07 (dd, J = 8.0, 1.0Hz, 4H), 3.91 (dd, J = 8.0, 1.0Hz, 4H).
[0083] Example 4
[0084]
[0085] Reaction process of compound 4:
[0086] 0.435 g of compound 1, 10 mL of chloroform and 0.504 g of m-CPBA were added to a three-necked flask, purged with argon for 30 minutes, and stirred at room temperature to react overnight.
[0087] Post-processing process:
[0088] Water was added to quench the reaction, and the product was extracted three times with ethyl acetate. The organic phases were combined, washed three times with deionized water and three times with saturated brine, anhydrous magnesium sulfate was added to remove water, the product was filtered, the liquid phase was concentrated by rotary evaporation, and the product was purified by column chromatography using n-hexane: ethyl acetate = 1:1 (volume ratio) as the eluent to obtain 0.45 g of a white solid with a yield of 91%.
[0089] Compound 4 is the crown ether-like compound, and its H NMR spectrum data is: 1 H NMR (500MHz, Chloroform-d) δ7.34(s,6H),7.20(d,J=12.5Hz,6H),6.75(s,6H),5.98(d,J=12.5Hz,6H),4.31(d,J=12.5Hz,5H),3.56(d,J=12.5Hz,5H).
[0090] Example 5
[0091] Compound 2 (30 mg) was dissolved in 1 mL of propylene carbonate, and then NaPF6 (138 mg) was added and stirred to dissolve. The resulting electrolyte was stirred at room temperature for 4 hours to allow it to be fully mixed until it became transparent and homogeneous. The transparent and homogeneous solution was allowed to stand at room temperature to obtain the high ionic conductivity electrolyte containing the crown ether-like additive.
[0092] Example 6
[0093] Compound 2 (8 mg) was dissolved in 1 mL of propylene carbonate, and then NaPF6 (138 mg) was added and stirred to dissolve. The resulting electrolyte was stirred at room temperature for 4 hours to allow it to be fully mixed until it became transparent and homogeneous. The transparent and homogeneous solution was allowed to stand at room temperature to obtain the high ionic conductivity electrolyte containing the crown ether-like additive.
[0094] Example 7
[0095] Compound 2 (13.5 mg) was dissolved in 1 mL of propylene carbonate, and then NaPF6 (138 mg) was added and stirred to dissolve. The resulting electrolyte was stirred at room temperature for 4 hours to allow it to be fully mixed until it became transparent and homogeneous. The transparent and homogeneous solution was allowed to stand at room temperature to obtain the high ionic conductivity electrolyte containing the crown ether-like additive.
[0096] Comparative Example 1
[0097] NaPF6 (168 mg) was dissolved in 1 mL of propylene carbonate, and all the electrolytes were stirred at room temperature for 4 hours to be fully mixed until they became transparent and homogeneous; the transparent and homogeneous solution was allowed to stand at room temperature to obtain the carbonate-based electrolyte.
[0098] Comparative Example 2
[0099] 18-crown ether 6 (30 mg) was dissolved in 1 mL of propylene carbonate, and then NaPF6 (138 mg) was added and stirred to dissolve. The resulting electrolyte was stirred at room temperature for 4 hours to allow it to be fully mixed until it became transparent and homogeneous. The transparent and homogeneous solution was allowed to stand at room temperature to obtain an electrolyte containing a crown ether additive.
[0100] Performance Test:
[0101] Figure 1 The LSV curves of the electrolytes of Example 5 and Comparative Example 1 are tested by three-electrode test, where the positive electrode is a sodium sheet, the negative electrode is silver / silver chloride, the reference electrode is a platinum wire electrode, and the test scanning speed is 1mv / s. Figure 1 As shown, as the voltage increases, the electrolyte begins to undergo oxidation reaction, where the oxidation voltage of carbonate is 3.9 V, and the oxidation voltage of the electrolyte with crown ether compound 2 added is 4.2 V, an increase of 7.7%. This result shows that after adding crown ether (also known as pseudo-crown ether), the aromaticity of crown ether makes the oxidation decomposition voltage of the electrolyte significantly improved.
[0102] Figure 2The long cycle performance test results of the soft-pack batteries prepared in Example 5 and Comparative Examples 1 and 2 are shown. The test conditions are as follows: the test voltage is 2-3.9V, and the cycle capacity retention rate is 13% higher after 250 cycles of cycling compared to the case without the addition of the crown ether at room temperature. The cycle capacity retention rate of the crown ether-like additive is still 92% after 250 cycles, which is 29% higher than that of the battery without the addition of the crown ether additive and 8% higher than that of the crown ether additive. This shows that the crown ether structure does effectively improve the solvation structure of the ions and prolongs the life of the battery. Compared with the crown ether, the crown ether-like structure described in the present invention has further improved the life of the battery, indicating that the crown ether-like compound described in the present invention retains the advantages of the crown ether. At the same time, the nitrogen oxide structure formed by pyridine and the like increases the ion coupling ability with the sodium ions, so that the ions can jump quickly between coordination sites, thereby further optimizing the performance of the battery.
[0103] Figure 3 This is the result of the electrolyte electrochemical impedance test. The test method is: three-electrode test, in which the positive electrode is a sodium sheet, the negative electrode is silver / silver chloride, and the reference electrode is a platinum wire electrode. As shown in the figure, after adding the crown ether-like additive, the impedance of the electrolyte has been significantly reduced, which shows that the additive contains the characteristics of the crown ether. The surface and interfacial activity of the aliphatic crown ether helps to improve the solubility of the electrolyte lithium salt in the electrolyte solvent, thereby improving the conductivity of the electrolyte and reducing the resistance.
[0104] It can be seen from the above embodiments that the electrolyte containing the crown ether compound additive shown in Formula I or Formula II described in the embodiments of the present invention is applied to sodium ion batteries, which can reduce the sodium ion concentration on the electrode surface, avoid sodium precipitation behavior, and extend the working life of the battery. The electrolyte containing the crown ether additive developed by the present invention overcomes the disadvantage that crown ethers cannot be prepared on a large scale. The prepared electrolyte can effectively avoid sodium precipitation behavior on the negative electrode surface and has high ionic conductivity. In addition, the crown ether additive is simple to synthesize and is conducive to large-scale production.
[0105] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A crown ether-like compound, characterized in that Having the structure of formula I or formula II:
2. A method for preparing a crown ether-like compound, characterized in that: The following steps are involved: The pentaerythritol is subjected to a substitution reaction with an ortho-halogenated nitrogen-containing heterocyclic substance to obtain an intermediate; the ortho-halogenated nitrogen-containing heterocyclic substance is an ortho-halogenated pyridine or an ortho-halogenated pyrrole; The intermediate is subjected to quaternary ammonium oxidation with an oxidant to obtain a crown ether-like compound as shown in Formula I or Formula II; 3. An electrolyte containing a crown ether-like compound, characterized in that: The invention comprises a non-aqueous organic solvent, a sodium salt and an additive, wherein the additive is the crown ether-like compound according to claim 1 or the crown ether-like compound obtained by the preparation method according to claim 2.
4. The electrolyte according to claim 3, characterized in that The sodium salt is selected from at least one of sodium hexafluorophosphate, sodium perchlorate, sodium tetrafluoroborate, sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium bis(oxalatoborate), sodium difluorophosphate, sodium difluorooxalatoborate and sodium difluorobis(oxalatophosphate).
5. The electrolyte according to claim 3, characterized in that The non-aqueous organic solvent is one or more of organic esters, C1-10 alkyl ethers, cyclic ethers, sulfones, dinitriles, and ionic liquids.
6. The electrolyte according to claim 5, characterized in that The organic esters are at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, 1,4-butyrolactone, methyl formate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate and ethyl butyrate; the C1-10 alkyl ethers are at least one of dimethyl ether, diethyl ether and methyl ethyl ether; the dinitriles are at least one of adiponitrile, succinonitrile and glutaronitrile; the sulfones are at least one of dimethyl sulfoxide and cyclopentane sulfone; and the ionic liquids are at least one of imidazole and pyrrole ionic liquids.
7. The electrolyte according to any one of claims 3 to 6, characterized in that: The non-aqueous organic solvent accounts for 60-85% of the weight of the electrolyte.
8. The electrolyte according to claim 7, characterized in that The sodium salt accounts for 8-25% of the electrolyte weight.
9. A sodium ion battery comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The electrolyte is the electrolyte containing a crown ether-like compound as described in any one of claims 3 to 8.
10. The sodium ion battery according to claim 9, characterized in that: The active material of the positive electrode is selected from layered oxides, Prussian blue or polyanions; the active material of the negative electrode is selected from at least one of graphite, hard carbon, silicon-carbon composite material and silicon monoxide.